Neuregulin-1, a potential protective for Cardiovascular repair (Review) - Sh. Al – Zuhairi, Wafaa Sh. Al – Zuhairi; Sadeghi , Leila; Abdallah Hassan, Ekhlas (ASJ - Academic Science Journal, 2024)
Abstract Neuregulin-1, or NRG 1, is a powerful cardiomyocyte proliferator that impacts the circulatory system. Endothelial cells in the bloodstream secrete and release it. It is essential for the development, proliferation, differentiation, apoptosis, and other cardiovascular functions of the heart. In the pathophysiology of several cardiovascular disorders, NRG 1 may repair the heart, including cardiomyopathy, and atherosclerosis, demonstrated by numerous experiments. Through the NRG 1 /ErbB pathway, NRG 1 can associate related signaling pathways, creating signal cascades to progress the microenvironment of myocardial by controlling necrotic apoptosis, oxidative stress, and cardiac inflammation. In this article, we provide an overview of recent developments in the molecular processes of NRG 1, clarify the role that targets NRG 1 in cardiovascular disease, and identify areas that require more investigation.